Edukasi Pemilihan Pangan Lokal Bergizi Pencegah Stunting di Paniki Atas, Minahasa Utara - Jaya Edy, Hosea; Mansauda, Karlah Lifie Riani; Tasiam , Ezrani (Jurnal Lentera: Penelitian dan Pengabdian Masyarakat, 2025)
Stunting remains a chronic nutritional problem faced by communities in Indonesia, including those in Paniki Atas, North Minahasa Regency. This community service activity aimed to enhance public understanding of stunting prevention through the utilization of nutritious local food resources. The method employed was counseling and interactive discussion involving pregnant women, breastfeeding mothers, and community health cadres, with materials covering the introduction of local nutritious foods, balanced menu planning, and healthy food processing practices. The results indicated high participant enthusiasm and a significant increase in knowledge, with the average score improving from 50% before the session to 90% after the counseling. This program contributes to raising nutritional awareness and fostering community self-reliance in utilizing local food resources as a sustainable effort to prevent stunting in the Paniki Atas area.